Fenomena Citizen Journalism di Banten (Best Practices Fesbuk Banten News dalam Membangun Gerakan Kepedulian Sosial melalui Emphatic Journalism) - Abdul Malik (LONTAR: Jurnal Ilmu Komunikasi, 2015)
This research was conducted to understand the movement of citizen journalism in building the spirit of social care through the application of the principle empathic journalism by fesbukbantennews.com commonly abbreviated FBN. On his way through the utilisation Facebook FBN able to collect tens of thousands of participate in various social awareness movement. This fact proves that the existence and progress of communication technology has led to social media. One of them, the presence of the Internet has spawned a variety of social media as embodied in the citizen journalism movement until the rise of social awareness movement itself. This is consistent with theory of technological determinism theory popularized by Marshal McLuhan that inventions in communication technology led to a cultural change, a change in the types of communication form of human life and we create tools for communication and finally the equipment to communicate the we use to form or affect our own lives.  Key Words: Citizen Journalism, Emphatic Journalism, Fesbukbantennews.com